Design of land management projects for development of crop rotations using geoinformational modeling - Кохан, Світлана Станіславівна; Шквир, Иван Николаевич; Москаленко, Антонина Анатольевна (Eastern-European Journal of Enterprise Technologies, 2014)
The problems of the heavy use of agricultural lands, leading to the development of degradation processes are defined. The necessity of automating a number of stages involving the development of land management projects for ensuring ecological and economic justifications of crop rotations and streamlining lands is shown. Composing blocks of the geo-information model for concerning the geo-imaging of eco-technology crop land groups, taking into account a potential hazard of erosion processes and the intensity of land use, are substantiated. Blocks of primary data, data processing and the presentation of modeling results are singled out. The developed algorithm of the geo-imaging of eco-technology crop land groups can significantly reduce the time limits of analyzing spatial data for decision-making and carrying out the project design work. The areas of eco-technology crop land groups by the example of a model household are determined, and the types of recommended crop rotations, crop groups and activities are distinguished.